Usp7 regulates Hippo pathway through deubiquitinating the transcriptional coactivator Yorkie - Sun, Xiaohan (Nat Commun, 2019)
The Hippo pathway plays an important role in organ development and adult tissue homeostasis, and its deregulation has been implicated in many cancers. The Hippo signaling relies on a core kinase cascade culminating in phosphorylation of the transcription coactivator Yorkie (Yki). Although Yki is the key effector of Hippo pathway, the regulation of its protein stability is still unclear. Here, we show that Hippo pathway attenuates the binding of a ubiquitin-specific protease Usp7 to Yki, which regulates Hippo signaling through deubiquitinating Yki. Furthermore, the mammalian homolog of Usp7, HAUSP plays a conserved role in regulating Hippo pathway by modulating Yap ubiquitination and degradation. Finally, we find that the expression of HAUSP is positively correlated with that of Yap, both showing upregulated levels in clinical hepatocellular carcinoma (HCC) specimens. In summary, our findings demonstrate that Yki/Yap is stabilized by Usp7/HAUSP, and provide HAUSP as a potential therapeutic target for HCC.